A Joint Hazard-Longitudinal Model of the Timing of Migration, Immigrant Quality, and Labor Market Assimilation - Apoorva Jain; Klara Sabirianova Peter (Institute of Labor Economics (IZA), 2017)
This paper develops and estimates a joint hazard-longitudinal (JHL) model of the timing of migration and labor market assimilation – two processes that have been assumed to be independent in the existing literature. The JHL model accounts for the endogenous age of entry in estimating the returns to years since migration by allowing cross-equation correlations of random intercepts with individual rates of wage assimilation. Commonly ignored sample selection issues due to non-random survey attrition and missing wages are also addressed. Using German household panel surveys from 1984 to 2014 and home country-level data from 1961, we find large upward bias in the OLS-estimated average rate of wage assimilation. Our estimates suggest that immigrants with lower unobserved skills and with a higher unobserved propensity to migrate early have a faster assimilation rate.
Keywords: J24; J31; J61; N30; C41; 330; migration; joint hazard-longitudinal model; mixed effects; random slope; individual-specific wage assimilation; unobserved skills; survival analysis; timing of migration; maximum likelihood; selection due to endogenous entry; Germany